"Bi‐Bi" technique for lip augmentation: A retrospective study on 30 cases. (19th July 2022) - Stéphane, Smarrito; Candice, Smarrito‐Menozzi; Florence, Brunel
Abstract: Introduction: Lip augmentation is achieved mainly by using hyaluronic acid (HA) fillers. The injection procedures are performed either superficially or deeply with a needle or a cannula, and only one type of hyaluronic acid is used. The authors' objective was to evaluate the feasibility, safety, and satisfaction level of a procedure combining two anatomical injection plans, two injection modes (i.e., cannula and needle), and two types of hyaluronic acid fillers. Method: The retrospective study included 30 patients who underwent the following procedure: Intramuscular retro‐trace injections of Stylage M (Vivacy® Laboratories) were conducted through a 27‐gauge cannula at the level of the upper and lower hemi‐lip. Then, intradermal injections of Stylage Lips (Vivacy® Laboratories) using a 33‐gauge needle were carried out on the entire lip border as well as the cupid's bow. During a post‐injection follow‐up, subjects were asked to evaluate satisfaction level and the effect of fillers over time. Elastic (G′) and viscosity (G″) moduli of HA fillers were measured with a rheometer (AR2000, TA Instruments) prior to and after extrusion through a 33‐gauge needle. Results: Rheological assessment showed that passage through a 33‐gauge needle did not alter the viscoelastic properties of HA fillers. After the clinical procedure, no side effects were observed except for standard post‐treatment bruises and edema. No vascular incident occurred. Moreover, overall patient satisfaction was high (2.6/3) and there was a long‐lasting perception of the effect of the filler. Conclusion: The current study demonstrated that dissociating the anatomical zones of the lip during the injection procedure by means of different hyaluronic acids in the muscular and dermal planes would efficiently and safely provide both lip projection and fullness for a natural and lasting effect.